Praanggapan pada dialog mengenai kejujuran: kajian Pragmatik dalam novel Asal Kau Bahagia karya Bernard Batubara - Prapti Wigati Purwaningrum; Lia Nurmalia (BAHASTRA, 2019)
The aims of this analysis is to examine presuppositions on dialogue about honesty through pragmatic studies. This is a qualitative study with content analysis method because this research prioritizes the content approach of dialogue in the novel. The data source of this analysis is a dialogues that contain presuppositions and imply honesty in the novel Asal Kau Bahagia by Bernard Batubara. Data provision of this analysis is done by using simak method that is applied through note-taking techniques. The results of this study indicate that 26 data containing presuppositions consisting of 9 data included in factive presuppositions, 3 lexical presuppositions data, 7 data as existantial presuppositions, 5 data as non-factual presuppositions, and 2 data are counterfactual presuppositions. In addition, the research also revealed that through several presupposition there was a message in each speech, the action would always be related to the value of honesty, but sometime it is really to be said. If it happens there is only prejudice and revenge exists. In addition, through this pragmatic, presupposition, and about honesty, the author also hopes that the results of this paper will be able to contribute ideas to the reading community about the importance of the value of honesty in friendship, romance, and in a society that has recently faded.